The effect of study habits and sex on academic performance - Jabonete, Rhea Lina R. (Tacloban City Rhea Lina R. Jabonete, 1999)
This study involved 120 high school students who were randomly chosen among the four different year levels of 387 high school students of Samar State Polytechnic College, Catbalogan, Samar AY 1998-1999. This study was conducted in order to test the effect of study habits and sex on academic performance. With this, the researcher conducted a Survey on Study Habit and Attitudes (SSHA), a 100-item inventory, among these students and secured their grades during the first and second grading periods. Since this study deals with two variables, namely: study habits and sex, the researcher made use of the two-factor analysis of variance (2x3, ANOVA) and SSHA- Form H and SSHA Diagnostic Profile in the analysis and interpretation of data. The researcher divided the 120 respondents according to their sex (60 males and 60 females). Each of 60 is further divided into three subgroups of 20 each according to the study habit category (poor, average, and excellent) the respondents belong. This study found out that at .05 level there is a significant relationship between study habits and academic performance. However, no satisfactory significant relationship was found between sex and academic performance as well as on the interaction between the two variables and academic performance.
Undergraduate thesis (B.A.S.S. Psychology) -- University of the Philippines, Tacloban.
Keywords: Academic performance; Social Science